Exploitation of the bait organism Upogebia africana (Crustacea: Anomura) in the Knysna estuary - Cretchley, Robyn (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1997)
In South African estuaries the anomuran mud prawn, Upogebia africana (Ortmann), is the main organism exploited as bait by recreational and subsistence anglers. In the Knysna estuary, three groups of bait collectors were identified on the basis of their source of income: subsistence fishermen who rely on bait-collecting and fishing for their income, supplementary anglers who catch fish to supplement their income and leisure anglers who draw no income from fishing. Two groups were identified based on the methods used: lelsure anglers who collect bait using a prawn pusher or pump and fish using a fishing rod and tackle, and non-leisure anglers who collect mud prawns using tin cans and fish with handlines. The hypothesis was erected that bait-collecting does not affect the U africana populations in the Knysna estuary. The approach adopted was to assess the distribution, density, population structure and reproductive patterns of the bait stock and to estimate the intensity of bait collection, to test the validity of the hypothesis. U africana has an extensive distribution, occupying 62 % of the available intertidal area of the Knysna estuary. Mud prawns have a broad intertidal distribution from the high water level (Spartina zone) to the shallow subtidal. The density, biomass and population structure of the mud prawns vary significantly with distance up the estuary and with tidal height on each shore. The Invertebrate Reserve supports very low densities of U africana (x = 11.7 mâ »Â²), whereas a relatively inaccessible centre bank in the middle reaches of the estuary appears to be a very effective natural mud prawn reserve as it supports the highest densities (x = 176.5mâ »Â²). The mud prawn stock of the estuary is estimated to be 2.19 x 108 prawns (82.7 tonnes dry mass). The numbers of bait collectors present per mudbank is highest on public holidays (x = 34) and higher during the summer holidays (x = 16) than during the winter (x = 4). A total of 1.858 x 106 U africana or 700.53 kg (dry mass) are removed by bait collectors annually from the 6 popular bait-collecting sites studied. This represents 8.49 % of the mud prawn stocks at these sites and 0.85 % of the entire estuary stock. 85 % of the U africana taken as bait annually, is removed by the 77.12 % of bait collectors who are non-leisure anglers. Recreational or leisure anglers are responsible for removing 14.2 %. The reproduction of female U africana in the Knysna estuary is seasonal and occurs from late July to April. There is evidence that this breeding season consists of two merging breeding cycles. The largest percentage (63 %) of ovigerous females is found in the middle reaches of the Knysna estuary at the Oyster Bank where the highest numbers of stage 1 larvae (165 mâ »Â³) are released. Larvae were exported from the estuary on the crepuscular ebb tide with peaks in abundance of nearly 1500 mâ »Â³ in November 1995 and January 1996. Although numbers caught are not significantly higher, larvae are nearly twice as abundant on crepuscular neap tides following a new moon (waxing quarter) than on those following a full moon (waning quarter). Recruitment of juvenile U africana to populations in the estuary was highest in December (45 mâ »Â²) and decreased over the summer. The highest numbers of recruits (31 mâ »Â²) were found at those sites closest to the mouth or on the main channel. Recruitment to the Leisure Isle and Thesens sites which are intensively exploited by bait collectors is high (20 - 32 mâ »Â²). The number of juveniles recruiting to U africana populations is estimated to be four times as high as the numbers of mud prawns taken by bait collectors. Legal methods of bait collection used in the Knysna estuary by the majority of anglers appear to cause minimal sediment disturbance and are not likely to affect the associated infauna. Illegal bait-collecting methods are however highly destructive and must be prohibited. It is concluded that the null hypothesis is acceptable, as mud prawn stocks of the Knysna estuary are not over-exploited and appear to be naturally regulated. The recruitment rate of juvenile U africana is estimated to be sufficiently high to sustain the present levels of exploitation.
Keywords: Upogebia africana -- South Africa -- Knysna; Mud shrimps -- South Africa -- Knysna; Fishing baits -- South Africa -- Knysna